앱 인벤터를 활용한 프로그래밍 교육이 예비 교사의 문제 해결 능력, 자아 효능감, 인식에 미치는 영향 - 김성원(Seong-Won Kim); 이영준(Youngjun Lee) (한국컴퓨터정보학회논문지, 2017)
The ability to use information technology has become increasingly important as technological advances continue to sweep through the computing world, and education for improving computational thinking has become globally instituted . In South Korea, informatics subjects have been modified in the 2015 curriculum and are now compulsory in primary and secondary education. However, despite substantial financial investment and numerous studies promoting informatics education, there continues to be a serious lack of pre-service teachers capable of teaching computational thinking. This study investigated pre-service teacher programming education using App Inventor, their perceptions of App Inventor, and how use of the program affected teacher problem-solving abilities and self-efficacy. In the pre-test, the control group and experimental group showed no statistically significant difference; however, the post-test revealed that the two groups showed statistically significant differences in problem-solving skills and self-efficacy. The participants initially showed interest in using App Inventor; however, after practice-teaching and project-based learning, the participants demonstrated a growing negativity toward the program when they made errors and the functional limits of App Inventor became apparent. Although most participants stated that they would not use App Inventor in their classes, the positive statistically significant differences in problem-solving skills and self-efficacy indicate that this study could be utilized as a basis for building a teaching-learning program using App Inventor and creating an educational plan for teaching computational thinking. KCI Citation Count: 2